전구체 내의 셀레늄 함유량이 CuInSe2 박막의 물성에 미치는 영향 - 박광훈; Gwang Hoon Park; 박재형; Jae Hyoung Park; 하준석; Jun Seok Ha; 고항주; Hang Ju Ko (대한금속·재료학회지, 51(11), 2013)
We studied the effect on physical properties of CuInSe2 (CIS) thin films by change of the Se content in Cu-In-Se precursors. The three kinds of precursors with different Se content were deposited by a hybrid sputtering system which was equipped with the Selenium Knudsen cell (Se K-cell). The precursors were heated in an Se atmosphere for 15 minutes at 425 ℃, which produced crystalline CIS films. We characterized the crystalline CIS films using scanning electron microscopy (SEM), energy-dispersive x-ray spectroscopy (EDS), x-ray diffraction (XRD), and a Hall effect measurement system. The size of the island in the CIS films was reduced with an increasing Se content in the Cu-In-Se precursors. We found that the island structure in the CIS films disappeared with precursors of Se content over 19 at%. We were able to make a highly adhesive CIS film to Mo back contacts by using precursors with Se content of 19 at%. The solar cells fabricated with the CIS films using precursors with an Se content of 19 at% achieved 8.2% efficiency.